The Effect of Musyarakah, Mudharabah, and Murabahah Financing on The Financial Performance of Sharia Commercial Banks in Indonesia - Afrizal, Yosa; Aliamin, Aliamin; Shabri, M. (Journal of World Science, 2023)
This study aims to determine the effect of musharakah, mudharabah, and murabahah financing on the financial performance of Sharia Commercial Banks in Indonesia. This type of research is quantitative research. This research uses secondary data in the form of annual financial reports of Sharia Commercial Banks in Indonesia for the period 2010-2019 sourced from the Financial Services Authority (OJK) website. Through purposive sampling technique, 11 bank samples were obtained which produced 96 observational data. The results of the analysis show that musharakah financing does not affect the financial performance (ROA) of Sharia Commercial Banks in Indonesia, while mudharabah and murabahah financing has a positive and significant effect on the financial performance (ROA) of Sharia Commercial Banks in Indonesia. it is concluded that the greater the value of musharakah financing distributed is not a guarantee that financial performance (ROA) will increase. This is because musharakah financing is financing with a profit-sharing system that has a very high risk where if the company experiences losses, the bank will also bear the loss of business run by entrepreneurs. Nevertheless, Islamic banking is expected to maintain and increase the amount of profit-sharing based financing such as musharakah.